2012
DOI: 10.17221/464/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Chasing after minerality, relationship to yeasts nutritional stress and succinic acid production

Abstract: Baroň M., Fiala J. (2012): Chasing after minerality, relationship to yeast nutritional stress and succinic acid production. Czech J. Food Sci., 30: 188-193. Minerality is certainly one of the most mysterious and most valuable tones of wine taste and it is very often associated with the concept of terroir. The isotachophoresis was used for determination of cations -minerals in two wines from vineyards with different soil conditions, with and without exceptional "minerality". However, it was found that it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…In the current study, succinic acid variations among strains was significantly higher than the 0.1 g/L increments used by Baron and Fiala (2012) under both the red and white wine settings (Fig 5A and 5B). As a result, the strain-dependent differences observed here are likely to affect the sensory properties of wines in a notable manner.…”
Section: Figurementioning
confidence: 45%
See 1 more Smart Citation
“…In the current study, succinic acid variations among strains was significantly higher than the 0.1 g/L increments used by Baron and Fiala (2012) under both the red and white wine settings (Fig 5A and 5B). As a result, the strain-dependent differences observed here are likely to affect the sensory properties of wines in a notable manner.…”
Section: Figurementioning
confidence: 45%
“…It has previously been shown that increasing the addition of succinic acid by 0.1 g/L in wines presents a detectable sensory impact to assessors (Baron & Fiala, 2012). In the current study, succinic acid variations among strains was significantly higher than the 0.1 g/L increments used by Baron and Fiala (2012) under both the red and white wine settings (Fig 5A and 5B).…”
Section: Figurementioning
confidence: 99%
“…The balance between these two acids might have an influence on the taste and flavor of the final product. Succinic acid gives a salty, slightly bitter, and desiccating feeling in the mouth (Peynaud 1984; Baron and Fiala 2012), whereas acetic acid induces a sour taste (Ishii et al 2009). The metabolite analysis results show that yeast can produce acetic acid and succinic acid in maximum levels of about 0.6 and 2.1 g/kg of flour, respectively, in fermenting dough.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies looked at the theoretical origin of minerality. Baroň & Fiala (2012) hypothesized that minerality could come from yeast metabolism during the fermentation of musts poor in nitrogen. From a geological perspective, according to Maltman (2013) the minerals in wine are nutrient elements (typically metallic cations) and are only distantly related to vineyard geological minerals, which are complex crystalline compounds.…”
Section: Introductionmentioning
confidence: 99%